A theory and method for combining multiple approaches for product customisation. (13th January 2006) - Hernandez, Gabriel; Allen, Janet K.; Mistree, Farrokh
A number of design techniques have been developed in recent years to improve the design of custom-made products, but no rigorous method has appeared until now to combine these techniques systematically. In this paper we describe a new method that addresses this issue, based on the formulation of the design of customisable products as a problem of optimal access in a geometric space. The method is illustrated with the design of a line of custom-made hand exercisers.